Coating agent for forming large-area perovskite thin film and method for forming large-area perovskite thin film using same
By using perovskite precursors, crystallinity enhancers and Lewis salt coating agents in perovskite solar cells, the problem of poor uniformity and thermal stability of perovskite films in large-area coating and mass production is solved. , realizes efficient and environmentally friendly perovskite film preparation, and improves the photoenergy conversion efficiency and production efficiency of solar cells.
Patent Information
- Application Number
- CN202380040629.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-17
- Publication Date
- 2024-12-27
AI Technical Summary
The existing perovskite films have poor uniformity and thermal stability during large-area coating and mass production, and the anti-solvent treatment process leads to environmental pollution and high costs, limiting the large-scale application of perovskite solar cells.
Using a coating agent containing perovskite precursor, crystallinity enhancer and Lewis salt, a large area perovskite film is formed without the use of anti-solvent through a scraper coating or spraying process, and the film is improved by annealing process. Phase stability and uniformity.
It is realized that large-area perovskite films with excellent uniformity and thermal stability are formed without using anti-solvent, reducing production costs and improving the photoenergy conversion efficiency and environmental friendliness of perovskite solar cells.
Smart Images

Figure CN119213086A_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a large-area perovskite film forming method for preparing a uniform large-area perovskite film without using an anti-solvent, a coating agent therefor, and a perovskite solar cell comprising the same as a light absorption layer. Background Art
[0002] In order to solve the global environmental problems caused by the depletion of fossil energy and its use, research on renewable clean alternative energy such as solar energy, wind energy, and hydropower is being actively carried out.
[0003] Among them, interest in solar cells that convert electricity directly from sunlight has greatly increased. Here, a solar cell refers to a cell that generates current-voltage by utilizing the photovoltaic effect of generating electrons and holes by absorbing light energy from sunlight.
[0004] Currently, solar cells based on np diode-type silicon (Si) single crystals with a light energy conversion efficiency exceeding 20% can be manufactured and applied to actual solar power generation, and there are also solar cells using compound semiconductors such as gallium arsenide (GaAs) with higher conversion efficiency than these. However, since these inorganic semiconductor-based solar cells require materials refined with high purity to achieve high efficiency, refining raw materials consumes a lot of energy, and expensive process equipment is required in the process of single crystal or thin film using raw materials, there are limitations in reducing the cost of solar cell manufacturing, which has been an obstacle to large-scale use.
[0005] Therefore, in order to manufacture solar cells at low cost, it is necessary to significantly reduce the cost of materials or manufacturing processes mainly used for solar cells. As an alternative to inorganic semiconductor-based solar cells, perovskite solar cells that can be manufactured with low-cost materials and processes are being studied.
[0006] The general structural formula of the perovskite structure is the AMX3 structure, which has an anion located at the X position, a large-sized cation located at the A position, and a small-sized cation located at the M position.
[0007] These perovskite compounds have excellent electrical conductivity, charge mobility and optical properties, and have a wide range of applications. They have various characteristics such as long life, high absorption wavelength spectrum due to small band gap and wide charge-carrier diffusion length. At the same time, they have the advantages of economical material price, can be made into solutions, low process cost, and can be manufactured by low-temperature processes. Therefore, they have attracted much attention as potential materials for renewable energy applications. In particular, research on perovskite solar cells using these perovskite compounds as light absorbers is ongoing.
[0008] Currently, most small-area (approximately 2.5 × 2.5 cm2 )’s perovskite film is based on spin coating technology, which is prepared by evenly coating the perovskite solution by spin coating and then using an anti-solvent to crystallize it.
[0009] Since the spin coating method has limitations in principle in large-area coating and mass production technology, doctor blade coating, slot die, inkjet printing, spray coating, etc. are generally used as a method for forming a thin film through a large-area process.
[0010] However, the perovskite thin film prepared by the above-mentioned large-area coating process is poor in uniformity and thermal stability, and due to the anti-solvent treatment process, the use of the anti-solvent leads to the generation of waste, etc., which has the limitation of reducing the mass productivity of perovskite. Summary of the invention
[0011] Technical issues
[0012] The present invention is developed to overcome the above problems, and aims to provide a method for forming a large-area perovskite film with excellent uniformity without performing an anti-solvent treatment process by introducing a coating agent with an optimal composition for forming a large-area perovskite film, and a coating agent used therefor.
[0013] Solutions to the problem
[0014] In order to solve the above problems, the present invention relates to a coating agent for forming a large-area perovskite film, which includes a perovskite compound represented by the following Chemical Formula 1, and includes a perovskite precursor, a crystallinity enhancer, a Lewis salt and a solvent.
[0015] [Chemical formula 1]
[0016] A m A' 1-m B(X n X' 1-n )3
[0017] In Chemical Formula 1, A is formamidinium (FA), ethylamine (EA), guanidine (GA) or ethylenediamine (EDA), and A' is Cs + 、Na + , K + NH4 + or Rb + , B is Pb 2+ Sn 2+ , Pd 2+ , Cu 2+ ,Ge 2+ , Sr 2+ 、Cd2+ 、Ca 2+ 、Ni 2+ 、Mn 2+ 、Fe 2+ 、Co 2+ 、Sn 2+ 、Yb 2+ or Eu 2+ ,X and X’ are each independently Cl - 、Br - or I - ,m and n are rational numbers satisfying 0 < m ≤ 1 and 0 < n ≤ 1, preferably, m and n are rational numbers satisfying 0.7 ≤ m ≤ 0.9 and 0.1 ≤ n ≤ 0.3.
[0018] As a preferred embodiment of the present invention, the above perovskite precursor may include an organic halide represented by the following Chemical Formula 2, a monovalent metal halide represented by the following Chemical Formula 3, a divalent metal halide represented by the following Chemical Formula 4, and a divalent metal halide represented by the following Chemical Formula 5.
[0019] [Chemical Formula 2]
[0020] AX
[0021] In Chemical Formula 2, A is formamidine (FA), ethylamine (EA), guanidine (GA), or ethylenediamine (EDA), and X is Br - or I - .
[0022] [Chemical Formula 3]
[0023] A’X
[0024] In Chemical Formula 3, A’ is Cs + 、Na + 、K + 、NH4 + or Rb + ,X is Cl - 、Br - or I - .
[0025] [Chemical Formula 4]
[0026] BX2
[0027] [Chemical Formula 5]
[0028] BX’2
[0029] In Chemical Formula 4 and Chemical Formula 5, B is Pb 2+ 、Sn 2+ 、Pd 2+ 、Cu 2+ 、Ge 2+ 、Sr2+ 、Cd 2+ , Ca 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ Sn 2+ , Yb 2+ or Eu 2+ , X and X' are each independently Cl - Br - or I - , X and X' are different halogen anions.
[0030] As a preferred embodiment of the present invention, the above-mentioned crystallinity enhancer may include at least one selected from CH3NH3Cl(MACl), CH3NH3Br and CH3NH3I.
[0031] As a preferred embodiment of the present invention, the Lewis salt may include at least one selected from N,N-dimethylpropyleneurea (DMPU), hexamethylphosphoramide (HMPA) and N-methyl-2-pyrrolidone (NMP).
[0032] As a preferred embodiment of the present invention, the solvent may include at least one selected from dimethylformamide (DMF), γ-butyrolactone, 2-methoxyethanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidinone (NMP).
[0033] As a preferred embodiment of the present invention, the coating agent of the present invention may include 15 mol % to 40 mol % of the crystallinity enhancer and 40 mol % to 100 mol % of the Lewis salt relative to 100 mol % of the perovskite precursor.
[0034] As a preferred embodiment of the present invention, the coating agent of the present invention may include the above-mentioned solvent and the above-mentioned Lewis salt in a volume ratio of 1:0.06-0.25.
[0035] Another object of the present invention relates to utilizing the above coating agent for large areas (200cm 2A method for forming a perovskite film of an area (larger than 1000 m) or larger can be performed by a process comprising the following steps: step 1, preparing a coating liquid comprising the above-mentioned coating agent for forming a thin film; step 2, forming a wet-thin film comprising mesophase crystallized perovskite by performing a coating process and drying on the upper part of a substrate with the above-mentioned coating liquid; and step 3, performing an annealing process on the above-mentioned wet film to form a large-area perovskite film comprising the perovskite compound represented by the above-mentioned chemical formula 1.
[0036] As a preferred embodiment of the present invention, the upper part of the substrate coated with the coating liquid may be a Si thin film layer, a hole transport layer, an electron transport layer and / or a passivation layer.
[0037] As a preferred embodiment of the present invention, the coating process can be performed by blade coating, slot die coating, rod coating, inkjet coating or spray coating.
[0038] As a preferred embodiment of the present invention, the above drying can be performed together with the coating process or after the coating process is completed.
[0039] As a preferred embodiment of the present invention, the drying may be performed by a knife blowing process to evaporate the solvent of the coating agent.
[0040] As a preferred embodiment of the present invention, the drying can be performed by an inert gas such as N2, Ar, or by a knife blowing process using an air knife to evaporate the solvent of the coating agent.
[0041] As a preferred embodiment of the present invention, the annealing may be performed by heat treatment at 120° C. to 180° C. for 5 minutes to 20 minutes.
[0042] Still another object of the present invention relates to a perovskite solar cell comprising a perovskite thin film formed by the above method using the above coating agent as a light absorbing layer (or photosensitive layer).
[0043] As a preferred embodiment of the present invention, the perovskite solar cell may be a tandem solar cell.
[0044] As a preferred embodiment of the present invention, the above-mentioned perovskite solar cell can be a stacked solar cell including an upper cell comprising a perovskite thin film formed by the above-mentioned coating agent for forming a large-area perovskite thin film as a light absorption layer; and a lower cell comprising Si, Cu(In,Ga)Se3, CdTe or a perovskite compound as a light absorption layer.
[0045] Effects of the Invention
[0046] The perovskite film forming method using the coating agent of the present invention does not require an anti-solvent treatment process, so it is environmentally friendly and has excellent mass production. In addition, the perovskite film prepared using the coating agent and the formation method of the present invention has excellent uniformity and thermal stability. By introducing it into the light absorption layer of a solar cell, a perovskite solar cell with high energy conversion efficiency can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 PL mapping measurement results performed in Experimental Example 1.
[0048] Figure 2a to Figure 2c This is a SEM measurement image performed in Experimental Example 2.
[0049] Figure 3 The UV-Vis and XRD measurement results performed in Experimental Example 3 are shown.
[0050] Figure 4 1 and 2 are side SEM measurement images for confirming the formation state of the perovskite thin film according to the mol % of the Lewis salt according to Examples 2 to 5 and Comparative Examples 1 and 3.
[0051] Figure 5 4 is a graph showing performance measurements of a single solar cell device according to the content of the crystallinity enhancing agent performed in Experimental Example 5.
[0052] Figure 6a and Figure 6b Graph showing performance measurements of a single solar cell device performed in Experimental Example 6.
[0053] Figure 7 1 is a performance measurement chart of the solar cell stack device performed in Experimental Example 6. DETAILED DESCRIPTION
[0054] Next, the present invention will be described in more detail by a method for forming a large-area perovskite film. Here, the large area refers to 200 cm 2 Area above, preferably, 250cm 2 The area above.
[0055] The present invention can form and obtain a large-area perovskite film through a process comprising the following steps: step 1, preparing a coating liquid containing a coating agent for forming a large-area perovskite film; step 2, forming a wet film containing mesophase crystallized perovskite by performing a coating process and drying on the upper part of a substrate with the above-mentioned coating liquid; and step 3, performing an annealing process on the above-mentioned wet film to form a large-area perovskite film containing a perovskite compound represented by the following chemical formula 1.
[0056] [Chemical Formula 1]
[0057] A m A’ 1-m B(X n X’ 1-n )3
[0058] In Chemical Formula 1, A is formamidine (FA), ethylamine (EA), guanidine (GA), or ethylenediamine (EDA), preferably FA, GA, or EDA, more preferably FA. Additionally, A’ in Chemical Formula 1 is Cs + , Na + , K + , NH4 + , or Rb + , preferably Cs + , Na + , or K + , more preferably Cs + .
[0059] B in Chemical Formula 1 is Pb 2+ , Sn 2+ , Pd 2+ , Cu 2+ , Ge 2+ , Sr 2+ , Cd 2+ , Ca 2+ , Ni 2+ , Mn 2+ , Fe 2+ , Co 2+ , Sn 2+ , Yb 2+ , or Eu 2+ , preferably Pb 2+ , Sn 2+ , Pd 2+ , or Cu 2+ , more preferably Pb 2+ , or Sn 2+ .
[0060] Additionally, X and X’ in Chemical Formula 1 are each independently Cl - , Br - , or I - , preferably, X is I - , and X’ is Br - . Also, m and n in Chemical Formula 1 are rational numbers satisfying 0 < m ≤ 1 and 0 < n ≤ 1, preferably rational numbers satisfying 0.7 ≤ m ≤ 0.9 and 0.1 ≤ n ≤ 0.3.
[0061] Generally, in A m A’ 1-mThe monovalent organic cation at the site is mixed with the monovalent inorganic cation to form a monovalent cation. Specifically, in Chemical Formula 1, A may include amine, ammonium, Group 1 metal, Group 2 metal and / or other cations or quasi-cation compounds, for example, may include formamidinium (hereinafter referred to as "FA"), methylammonium (hereinafter referred to as "MA") and FAMA.
[0062] MA-based perovskites, in which MA accounts for the majority of the composition, can be coated without an antisolvent and are suitable from the perspective of mass production, but have a fatal problem of not being able to ensure thermal stability.
[0063] On the other hand, FA-based perovskites, which currently hold the highest efficiency records, have poor phase stability, so antisolvent-free processes are limited and uniform large-area thin-film coating is difficult to achieve.
[0064] According to one embodiment of the present invention, in A m A' 1-m B(X n X' 1-n )3, in order to ensure the thermal stability of the light absorbing layer, methylammonium (MA) is not added, and the phase stability problem of FA-based perovskite is solved by optimizing the mixed composition. Specifically, the present invention aims to stabilize the crystal structure without reducing the thermal stability of the perovskite by introducing a small amount of Group 1 metal cations into MA-free metal halide perovskite, thereby ensuring phase stability.
[0065] In order to achieve the above effect, the composition (1-m) of the metal cations of Group 1 can be controlled to be above 0.1, and considering the band gap of the stacked device, the composition (1-m) of the metal cations can be controlled to be below 0.3. Therefore, the band gap of the perovskite material can be 1.50 eV to 1.80 eV, preferably, 1.55 eV to 1.72 eV.
[0066] The coating agent for forming a perovskite thin film of the present invention comprises a perovskite precursor, a crystallinity enhancer, a Lewis salt and a solvent.
[0067] In the coating agent composition, the above-mentioned perovskite precursor includes an organic halide represented by the following chemical formula 2, a monovalent metal halide represented by the following chemical formula 3, a divalent metal halide (first divalent metal halide) represented by the following chemical formula 4, and a divalent metal halide (second divalent metal halide) represented by the following chemical formula 5.
[0068] [Chemical formula 2]
[0069] AX
[0070] In Chemical Formula 2, A is formamidine (FA), ethylamine (EA), guanidine (GA) or ethylenediamine (EDA), preferably FA, GA or EDA, more preferably FA. In addition, X in Chemical Formula 2 is Br - or I - .
[0071] [Chemical formula 3]
[0072] A'X
[0073] In chemical formula 3, A' is Cs + 、Na + , K + NH4 + or Rb + , preferably Cs + 、Na + or K + , more preferably Cs + And, X in Chemical Formula 3 is Br - or I - .
[0074] [Chemical formula 4]
[0075] BX2
[0076] [Chemical formula 5]
[0077] BX'2
[0078] In Chemical Formula 4 and Chemical Formula 5, B is Pb 2+ Sn 2+ , Pd 2+ , Cu 2+ ,Ge 2+ , Sr 2+ 、Cd 2+ , Ca 2+ 、Ni 2+ , Mn 2+ , Fe 2 +、Co 2+ Sn 2+ , Yb 2+ or Eu 2+ , preferably Pb 2+ Sn 2+ , Pd 2+ Cu 2+ , more preferably Pb 2+ or Sn 2+ Furthermore, X in Chemical Formula 4 and X' in Chemical Formula 5 are each independently Cl - Br - or I - , preferably Br - or I- , X and X' are different halogen anions.
[0079] The crystallinity enhancer in the above-mentioned perovskite coating composition serves to increase the phase stability of the perovskite and improve the crystallinity by increasing the particle size of the perovskite crystal. The above-mentioned coating agent may include 15 mol% to 40 mol% of the crystallinity enhancer relative to 100 mol% of the above-mentioned perovskite precursor, and preferably, may include 15.5 mol% to 25.0 mol% of the crystallinity enhancer.
[0080] At this time, if the content of the crystallinity enhancer is less than 15 mol%, there may be a problem that the perovskite crystals cannot be formed in a sufficient size, and if the content of the crystallinity enhancer exceeds 40 mol%, the crystals may not be formed uniformly due to excessive use, resulting in the problem of uneven formation of the surface of the perovskite film.
[0081] As the above-mentioned crystallinity enhancer, it can include at least one selected from CH3NH3Cl (MACl), CH3NH3Br (MABr) and CH3NH3I (MAI), preferably, it can include at least one selected from MACl and MABr, preferably, it can include MACl.
[0082] The crystallinity enhancer is decomposed and removed during the annealing process of step 3 of the thin film formation process. Taking MACl as an example, it is removed in the form of MA gas and HCl during the annealing process, so that it will not remain in the perovskite crystal.
[0083] The Lewis base in the perovskite coating agent composition in step 1 is added to increase the phase stability of the perovskite and prevent the formation of pinholes in the film. Polar aprotic compounds can be used, preferably, at least one selected from N, N-dimethyl-propylene urea (DMPU), hexamethylphosphoramide (HMPA) and N-methyl-2-pyrrolidone (NMP), preferably, DMPU.
[0084] In the coating agent, the content of the Lewis salt is 40 mol % to 100 mol %, preferably 40 mol % to 90 mol %, and more preferably 50 mol % to 85 mol %, relative to 100 mol % of the perovskite precursor. At this time, if the content of the Lewis salt is less than 40 mol %, the binding energy of the perovskite crystal intermediate phase in the wet film formed by drying in the film formation process is weak, so the perovskite crystal phase cannot be smoothly formed, and the uniformity of the film will be poor. If the content of the Lewis salt exceeds 100 mol %, the perovskite crystallization is not smooth due to supersaturation, resulting in the problem of forming an uneven film. Therefore, in the present invention, the content of the Lewis salt in the coating agent is controlled within the above range.
[0085] The solvent in the above-mentioned perovskite coating agent composition may include at least one selected from dimethylformamide (DMF), γ-butyrolactone, 2-methoxyethanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP), preferably, it may include at least one selected from DMF, γ-butyrolactone and 2-methoxyethanol, and more preferably, it may include DMF.
[0086] Furthermore, as the amount of the solvent used in the coating agent, the above-mentioned solvent and the above-mentioned Lewis salt are used in a volume ratio of 1:0.06 to 0.25, preferably, the above-mentioned solvent and the above-mentioned Lewis salt are used in a volume ratio of 1:0.10 to 0.22, and more preferably, the above-mentioned solvent and the above-mentioned Lewis salt are used in a volume ratio of 1:0.10 to 0.18. If the content of the solvent relative to the Lewis salt is too much, pinholes may be generated in the film. If the content of the solvent relative to the Lewis salt is too little, the coating property cannot be ensured, and there is a problem of a significant increase in surface roughness. Therefore, in the present invention, the solvent content in the coating agent is controlled within the above-mentioned range.
[0087] Next, the substrate in step 2 of the large-area perovskite film formation method of the present invention refers to the object coated with the coating liquid in step 1, and the above-mentioned coating liquid can be coated on the top of the Si film, the top of the hole transport layer, the top of the electron transport layer or the top of the passivation layer.
[0088] In addition, the coating process in step 2 can be performed by blade coating, slot die coating, rod coating, inkjet coating or spray coating, preferably, by blade coating, slot die coating or rod coating.
[0089] In addition, the above-mentioned drying in step 2 can be carried out together with the coating process, or can be carried out as a separate process after the coating process is completed. As a preferred example of the drying method, it can be dried by an inert gas such as N2, Ar, or by an air knife. The solvent in the coating agent can be evaporated by drying, thereby forming a wet film of perovskite containing intermediate phase crystals.
[0090] Next, the above-mentioned annealing in step 3 of the method for forming a large-area perovskite film of the present invention can be achieved by heat treatment at 120° C. to 180° C. for 5 minutes to 20 minutes, preferably, heat treatment at 130° C. to 160° C. for 7 minutes to 15 minutes. In the annealing process, as described above, the crystallinity enhancer is removed by vaporization or the like. For example, the perovskite film is formed by the reaction shown in the following reaction formulas 1 to 5, and the crystallinity enhancer can be removed by evaporation.
[0091] [Reaction formula]
[0092] 1.PbCl2+FAI+2MAI→FAPbl3+MACI (evaporation removal)
[0093] 2. PbI2+FAI+MACl→FAPbl3+MACI (evaporation removal)
[0094] 3.PbI2+FABr+MACl→FAPbl2Br+MACI (evaporation removal)
[0095] 4.PbCl2+FABr+2MABr→FAPbBr3+MACI (evaporation removal)
[0096] 5.PbBr2+FABr+2MAI→FAPbBr3+MAI (evaporation removal)
[0097] By performing the above steps 1 to 3, a uniform large-area thin film including the perovskite compound represented by the above Chemical Formula 1 and having excellent thermal stability can be manufactured in a mass production process.
[0098] The present invention forms a light absorbing layer of a solar cell by using the coating agent and method for forming a perovskite film, and can provide a perovskite solar cell with excellent light conversion efficiency (power conversion efficiency, Power Conversino Efficiency, PCE). The perovskite solar cell of the present invention can be a pin structure perovskite solar cell, an inverted structure perovskite solar cell, a stacked perovskite solar cell or a stacked silicon / perovskite heterojunction solar cell.
[0099] For example, in a tandem solar cell composed of a silicon lower cell and a perovskite upper cell, the perovskite light absorbing layer can be formed as the light absorbing layer of the upper cell using the coating agent and method of the present invention.
[0100] In addition, in a stacked solar cell consisting of a lower cell including Cu(In,Ga)Se3, CdTe or a perovskite compound as a light absorption layer and a perovskite upper cell, the perovskite light absorption layer of the upper cell can also be formed by the above-mentioned coating agent and method of the present invention.
[0101] The recombination layer is a layer that induces recombination of electrons and holes generated in the above-mentioned lower battery and the light absorption layer to be described below, and can be a transparent film deposited with indium tin oxide (Induim Tin Oxide, ITO), fluorine doped tin oxide (Fluorinedoped Tin Oxide, FTO), Sb2O3 doped tin oxide (Sb2O3 doped Tin Oxide, ATO), gallium doped tin oxide (Gallium doped Tin Oxide, GTO), tin doped zinc oxide (tin doped zinc oxide, ZTO), ZTO:Ga (gallium doped ZTO), indium gallium zinc oxide (Indium gallium zinc oxide, IGZO), indium doped zinc oxide (Indium doped zinc oxide, IZO) or aluminum doped zinc oxide (Aluminum doped zinc oxide, AZO).
[0102] In addition, as an example of forming a composite layer, when a silicon solar cell doped with n-type or p-type impurities is used as the lower cell, the SiO2 is removed by treating the silicon solar cell doped with n-type or p-type impurities with hydrofluoric acid. x The oxide film is removed, and then the residual hydrofluoric acid is removed with ultrapure water. A composite layer can be formed on the upper end of the silicon solar cell with the oxide film removed by a sputtering process.
[0103] The hole transport layer (HTL) may include inorganic and / or organic hole transport materials. The inorganic hole transport material may include a material selected from nickel oxide (NiO x ), at least one of CuSCN, CuCrO2 and CuI.
[0104] The above-mentioned organic hole transport material may include carbazole derivatives, polyaryl alkane derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, styryl anthracene derivatives, fluorene derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, aromatic tertiary amine compounds, styrylamine compounds, aromatic dimethylimine compounds, porphyrin compounds, phthalocyanine compounds, polythiophene derivatives, polypyrrole derivatives, polyparaphenylene vinylene derivatives, pentacene, coumarin 6 (coumarin 6, 3-(2-benzothiazolyl)-7-(diethylamino)coumarin), ZnPC (zinc phthalocyanine), CuPC (copper phthalocyanine), TiOPC (titanium oxide phthalocyanine), oxidephthalocyanine), Spiro-MeOTAD (2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), F16CuPC (copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine),
[0105] phthalocyanine), SubPc (boron subphthalocyanine chloride), N3 (cis-di(thiocyanato)-bis(2,2'-bipyridyl-4,4'-dicarboxylic acid)-ruthenium(II), P3HT (poly[3-hexylthiophene]), MDMO-PPV (poly[2-methoxy-5-(3',7'-dimethyloctyloxyl)]-1,4-phenylene vinylene), vinylene), MEH-PPV (poly[2-methoxy-5-(2”-ethylhexyloxy)-p-phenylene vinylene), P3OT (poly(3-octyl thiophene), POT (poly(octyl thiophene), P3DT (poly(3-decyl thiophene), P3DDT (poly(3-dodecylthiophene), PPV (poly(p-phenylene vinylene), TFB (poly(9,9'-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine), amine)), polyaniline, Spiro-MeOTAD ([2,22′,7,77′-tetrakis(N,N-dimethoxyaniline)-9,9,9′-spirobis(fluoro)amine) ([2,22′,7,77′-tetrkis(N,N-dI -pmethoxyphenylamine)-9,9,9′-spirobifluorine]), CuSCN, CuI, PCPDTBT (Poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]]), SI - PCPDTBT (poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl]) ), PBDTTPD (poly((4,8-diethylhexyloxyl)), PFDTBT (poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7,-di-2-thienyl-2',1',3'-benzothiadiazole)] - 2-thienyl-2',1',3'-benzothiadiazole)])), PFO-DBT (poly[2,7-.9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)] -PSiFDTBT (poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl) diyl])), PCDTBT (Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl])), PFB (Poly( 9,9'-dioctylfluorene-co-bis(N,N'-(4,butylphenyl)bis(N,N'-phenyl-1,4-phenylene)diamine), F8BT (poly(9,9'-dioctylfluorene-cobenzothia diazole)), PEDOT (poly(3,4-ethylenedioxythiophene)), PEDOT:PSS (poly(3,4-ethylenedioxythiophene)poly(styrenesulfonate)), PTAA (poly(triarylamine)), 2-PACz and / or MeO-2PACz.
[0106] In addition, a method for forming the above-mentioned hole transport layer may include a coating method, a vacuum deposition method, etc., and examples of the coating method include a gravure coating method, a rod coating method, a printing method, a spray coating method, a spin coating method, a dip coating method, a die coating method, etc.
[0107] Next, the light absorbing layer is a large-area thin film layer formed by the coating agent and method of the present invention, which may include the perovskite crystal represented by the above Chemical Formula 1.
[0108] On the other hand, a protective layer (not shown in the figure) may be included between the hole transport layer and the light absorption layer. Specifically, the protective layer may include a carbazole body having a strong hole collection ability and a phosphonic acid group having a strong bonding force with the metal oxide, preferably, 2-PACz, MeO-2PACz, Br - SAM materials such as 2PACz, Me-4PACz, MeO-4PACz, 6-PACz, etc.
[0109] Methods for forming a protective layer include coating and / or vacuum deposition, and examples of coating methods include gravure coating, rod coating, printing, spraying, spin coating, blade coating, dip coating, and die coating, and preferably, a protective layer can be formed on one side of the hole transport layer by vacuum deposition.
[0110] Next, the electron transport layer may include an inorganic material (e.g., a metal oxide) and / or an organic material. The electron transport layer may be a flat metal oxide layer, a metal oxide layer with a concave-convex surface, a metal oxide layer or a porous metal oxide layer having a composite structure of the same or different types of metal oxide nanostructures (including metal oxide particles, nanowires and / or nanotubes) formed on the surface of a thin film-shaped metal oxide, preferably, a dense (compact) metal oxide layer and a porous (meso-porous) metal oxide layer may be included, as a preferred example, SnO2, TiO2, ZnO, etc. In addition, the organic material may include PCBM.
[0111] On the other hand, a buffer layer may be further included between the electron transport layer and the light absorption layer. The buffer layer is formed to prevent interface defects and improve transport capacity, and may include at least one selected from C60, PCBM and PC71BM.
[0112] Methods for forming a buffer layer include coating and / or vacuum deposition, and examples of coating methods include gravure coating, rod coating, printing, spraying, spin coating, blade coating, dip coating, and die coating, and according to one embodiment, a protective layer can be formed on one side of the light absorbing layer by vacuum deposition.
[0113] In addition, in the construction of the solar cell, the above-mentioned upper electrode (or source electrode) can be formed by coating or depositing at least one material selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C and a conductive polymer.
[0114] In addition, the solar cell may further include a passivation layer located between the light absorbing layer and the electron transporting layer.
[0115] The present invention will be described in more detail by the following examples, but the following examples should not be construed as limiting the scope of the present invention but should be construed as helping to understand the present invention.
[0116] [Example]
[0117] Example 1: Preparation of perovskite coating agent and perovskite film
[0118] After DMF as a solvent was added to a conical flask, the perovskite precursor was added and stirred to dissolve.
[0119] At this time, as the above-mentioned perovskite precursor, FAI powder (organic halide), CsBr powder (metal halide), PbI2 powder and PbBr2 powder were added at a molar ratio of 1:1:0.25:0.25.
[0120] Furthermore, 25 mol % of CH 3 NH 3 Cl (crystallization enhancer) and 50 mol % of DMPU (Lewis salt) were added to 100 mol % of the above perovskite precursor and stirred to prepare a coating agent for thin film formation.
[0121] Next, on 16×16cm 2 The coating agent is applied by a knife coater to the upper side of one surface of an ITO glass substrate, and then N2 is purged by an air knife to dry the coating agent, thereby forming a wet film of perovskite containing mesophase crystals.
[0122] Subsequently, the glass substrate on which the wet film was formed was annealed at 150° C. for 10 minutes to form a perovskite thin film including a perovskite compound represented by the following Chemical Formula 1-1 with a thickness of 550 nm.
[0123] [Chemical formula 1-1]
[0124] A m A' 1-m B(X n X' 1-n )3
[0125] In chemical formula 1-1, A is FA (formamidine), A' is Cs + , B is Pb 2+ , X is I - , X' is Br - , m=0.8, n=0.8.
[0126] Comparative Example 1
[0127] The perovskite coating agent was prepared in the same manner as in Example 1, except that Lewis salt was not used in the preparation of the coating agent, and a perovskite thin film was formed on the glass substrate using the coating agent.
[0128] Comparative Example 2
[0129] The perovskite coating agent was prepared by the same method as in Example 1, except that 50 mol % of DMSO, which is the substance showing the highest efficiency in the current spin coating process, was used instead of DMPU as a Lewis salt when preparing the coating agent. The perovskite coating agent was used to form a perovskite film on the above-mentioned glass substrate.
[0130] Table 1
[0131]
[0132] Experimental Example 1: PL mapping (micro photoluminescence mapping) measurement
[0133] PL mapping was performed on the perovskite films prepared in Example 1 and Comparative Examples 1 to 2, and the results are as follows: Figure 1 shown.
[0134] exist Figure 1 In the figure, a is a measurement image of the film surface of Comparative Example 1, b is a measurement image of the film surface of Comparative Example 2, and c is a measurement image of the film surface of Example 1. In the case of Comparative Example 1, the film surface looks uniform, but in fact, no perovskite film is formed on the whole, so it appears relatively uniform.
[0135] In the case of Comparative Example 2, it was confirmed that there were problems with the area (white part) coated because the perovskite was locally well formed and the area (black part) not coated because the perovskite was not well formed. On the other hand, it was confirmed that a perovskite thin film having a uniform surface as a whole was formed in Example 1.
[0136] Experimental Example 2: Scanning electron microscope (SEM) measurement
[0137] The SEM measurements of the perovskite films prepared in Example 1 and Comparative Examples 1 to 2 were performed, and the results are as follows: Figure 2a (Comparative Example 1), Figure 2b (Comparative Example 2) and Figure 2c (Example 1) shown.
[0138] Reference Figure 2aIt can be confirmed that in the case of the large-area perovskite film of Comparative Example 1 prepared without using Lewis salt, a large number of pinholes are formed, resulting in a problem that coverage cannot be ensured over the entire area.
[0139] In addition, refer to Figure 2b In the large-area perovskite film of Comparative Example 2 using DMSO as the Lewis salt, although some parts of high-quality films were formed (f), a large number of pinholes occurred as in Comparative Example 1, resulting in the problem that the film could not be formed (d, e).
[0140] On the other hand, refer to Figure 2c According to g, h and i, the large-area perovskite film of Example 1 has excellent film uniformity and no pinholes are generated. This is because, with the help of DMPU (Lewis salt) having strong binding energy with the perovskite precursor, the film is uniformly coated, and the perovskite crystallinity and binding force are improved, so pinholes will not be formed even if a large area is coated, and a uniform film can be formed.
[0141] Experimental Example 3: Ultraviolet-visible spectroscopy (UV-Vis) and X-ray diffraction (XRD) measurements
[0142] The perovskite film prepared in Example 1 was measured by UV-Vis, and the results are as follows: Figure 3 a (absorbance) and Figure 3 As shown in b (band gap).
[0143] The energy band gap is calculated from absorbance measurements.
[0144] Energy band gap (E g ) is 1.682 eV, which can be confirmed to meet the energy band gap (1.5 eV ≤ E) required for the perovskite light absorption layer of the upper cell device used in the stacked silicon / perovskite heterojunction solar cell. g ≤1.8eV).
[0145] In addition, XRD measurements were performed on the perovskite film prepared in Example 1, and the results are as follows: Figure 3 The results of XRD measurement confirmed that cubic phase perovskite crystals were well formed in the film.
[0146] Examples 2 to 5 and Comparative Example 3
[0147] The perovskite coating agent was prepared and the perovskite thin film was formed on the glass substrate using the same method as in Example 1, except that 40 mol% of DMPU as a Lewis salt was used in Example 2, 60 mol% of DMPU was used in Example 3, 80 mol% of DMPU was used in Example 4, and 100 mol% of DMPU was used in Example 5, as shown in Table 2 below. In addition, 20 mol% of DMPU was used in Comparative Example 3.
[0148] Table 2
[0149]
[0150]
[0151] Experimental Example 4: Scanning Electron Microscope (SEM) Measurement
[0152] In order to confirm the formation state of the perovskite film according to the mol% of the Lewis salt, the cross-sections of the films prepared in Examples 2 to 5 and Comparative Examples 1 and 3 were measured by SEM, and the image measurement results are as follows: Figure 4 As shown in a to f.
[0153] (a: Comparative Example 1, b: Comparative Example 3, c: Example 2, d: Example 3, e: Example 4, f: Example 5)
[0154] Reference Figure 4 It was confirmed that in Comparative Example 1 (0 mol%) and Comparative Example 3 (20 mol%), in which the content of DMPU as Lewis salt was less than 40 mol%, there were cave-like pinholes and the film was not formed uniformly. On the other hand, it was confirmed that in Examples 2 to 5, in which the content of DMPU was 40 mol% to 100 mol%, there were no pinholes and a uniform film was formed.
[0155] Examples 6 to 8 and Comparative Example 4: Preparation of perovskite films according to the content of crystallinity enhancer
[0156] As shown in Table 3 below, perovskite films were prepared using 30 mol%, 20 mol% and 15 mol% of CH3NH3Cl as a crystallinity enhancer in Examples 6, 7 and 8, respectively, and 10 mol% of CH3NH3Cl as a crystallinity enhancer in Comparative Example 4. The same method as in Example 1 was used to prepare the perovskite coating agent and form the perovskite film on the glass substrate.
[0157] Table 3
[0158]
[0159] Experimental Example 5: Performance Measurement of Solar Cell Devices
[0160] Opaque devices were fabricated by varying the content of MACl as a crystallinity enhancer in the range of 10 mol % to 30 mol %, and IV measurements were performed. The results are shown in Tables 4 and Figure 5 Refer to Table 4 and Figure 5 , the average efficiency in Examples 6 to 8 is roughly similar between 15 mol% and 30 mol%, and is 18.35% at 25 mol%, showing the result with the smallest deviation. This is because the commonly known crystallinity enhancer plays a role in helping particle growth, so it can be said that dense large particles are formed as a characteristic of perovskite. On the other hand, it can be confirmed that in the case of Comparative Example 4 in which the content of the crystallinity enhancer is less than 15 mol%, the terminal characteristics (V oc , J sc , FF), so the final conversion efficiency does not reach the conversion efficiency of Example 1 and Examples 6 to 8.
[0161] Table 4
[0162]
[0163] Manufacturing Example 1-1: Manufacturing of Perovskite Solar Cell
[0164] Using the coating agent for forming a perovskite thin film prepared in Example 1, an opaque perovskite solar cell unit (effective area: 0.096 cm 2 Specifically, as a single opaque device structure, on an organic substrate deposited with ITO (100 nm), NiO x (17nm), 2PACz (1nm), perovskite film (550nm), LiF (1nm), C60 (13nm), BCP (8nm), Ag electrode (200nm).
[0165] Manufacturing Example 1-2: Manufacturing of Perovskite Solar Cell
[0166] Except that the coating agents of Examples 2 to 5, Comparative Examples 1 and 3 were used instead of the coating agent of Example 1, an opaque calcium ore solar cell (effective area: 0.096 cm 2 ), a single perovskite solar cell device is manufactured in the same manner as in the above-mentioned Manufacturing Example 1 to carry out Manufacturing Examples 1-2 to 1-5, Comparative Manufacturing Example 1-1 and Manufacturing Example 1-2 (refer to Table 5 below).
[0167] Manufacturing Example 2: Manufacturing of a laminated silicon / perovskite heterojunction solar cell
[0168] The coating agent for forming a perovskite film prepared in Example 1 was used to manufacture a silicon / perovskite heterojunction solar cell stack device (effective area: 242.74 cm 2 The structure of the manufactured stacked device is as follows, that is, ITO (20nm) / NiO on the Si bottom device x (17nm) / 2PACz(1nm), perovskite film(550nm) / LiF(1nm) / C60(13nm) / SnO x (6nm) / ITO(50nm) / Ag(200nm).
[0169] Experimental Example 6: Performance Measurement of Solar Cell Devices
[0170] The current-voltage characteristics and efficiencies of the solar cells prepared in Manufacturing Examples 1-1 to 1-5, Comparative Manufacturing Examples 1-1 to 1-2, and Manufacturing Example 2 were measured. The results are shown in Tables 5 and 6 below. The performance measurement charts are shown in Table 5. Figure 6a (Single device, manufacturing example 1-1), Figure 6b (Single device, Manufacturing Examples 1-2 to 1-5, Comparative Manufacturing Examples 1-1 to 1-2) and Figure 7 (Stacked device) as shown.
[0171] Table 5
[0172]
[0173] Table 6
[0174]
[0175] Referring to Tables 5 and 6 above, it can be confirmed that Comparative Manufacturing Examples 1-1 and 1-2, which introduce a perovskite coating with a DMPU content of less than 40 mol% as a Lewis salt as a light absorbing layer, have a photoelectric conversion efficiency of less than 10.50%, which is relatively very low compared to Manufacturing Examples 1-1 to 1-5.
[0176] On the other hand, it can be confirmed that the photoelectric conversion efficiency of Production Examples 1-1 to 1-5 is 15.0% or more, preferably 16.0% or more, and Production Example 1-1 including a light absorbing layer formed of the coating agent of Example 1 with a DMPU content of 50 mol% exhibits the most excellent solar cell performance.
[0177] Through the above embodiments and experimental examples, it can be confirmed that large-area perovskite thin films without pinholes and with guaranteed uniformity can be commercially manufactured, and the perovskite solar cells manufactured using the thin films have high photoelectric conversion efficiency.
Claims
1. A coating agent for forming a large-area perovskite thin film, which is a coating agent for forming a thin film comprising a perovskite compound represented by the following chemical formula 1, characterized in that: Including perovskite precursor, crystallinity enhancer, Lewis salt and solvent: [Chemical formula 1] A m A’ 1-m B(X n X’ 1-n )3 In Chemical Formula 1, A is formamidine, ethylamine, guanidine or ethylenediamine, and A' is Cs + 、Na + , K + NH4 + or Rb + , B is Pb 2+ Sn 2+ , Pd 2 + , Cu 2+ ,Ge 2+ , Sr 2+ 、Cd 2+ , Ca 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ Sn 2+ , Yb 2+ or Eu 2+ , X and X' are each independently Cl - Br - or I - , m and n are rational numbers satisfying 0.7≤m≤0.9 and 0.1≤n≤0.
3.
2. The coating agent for forming a large-area perovskite film according to claim 1, characterized in that: The perovskite precursor includes an organic halide represented by the following chemical formula 2, a monovalent metal halide represented by the following chemical formula 3, a divalent metal halide represented by the following chemical formula 4, and a divalent metal halide represented by the following chemical formula 5: [Chemical formula 2] AX In Formula 2, A is formamidine, ethylamine, guanidine or ethylenediamine, and X is Br - or I - , [Chemical formula 3] A'X In chemical formula 3, A' is Cs + 、Na + , K + NH4 + or Rb + , X is Cl - Br - or I - , [Chemical formula 4] BX2 [Chemical formula 5] BX'2 In Chemical Formula 4 and Chemical Formula 5, B is Pb 2+ Sn 2+ , Pd 2+ , Cu 2+ ,Ge 2+ , Sr 2+ 、Cd 2+ , Ca 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ Sn 2+ , Yb 2+ or Eu 2+ , X and X' are each independently Cl - Br - or I - , X and X' are different halogen anions.
3. The coating agent for forming a large-area perovskite film according to claim 1, characterized in that: The crystallinity enhancer comprises at least one selected from CH3NH3Cl, CH3NH3Br and CH3NH3I, The Lewis salt comprises at least one selected from N,N-dimethylpropylene urea (DMPU), hexamethylphosphoramide (HMPA) and N-methyl-2-pyrrolidone (NMP), The solvent includes at least one selected from dimethylformamide (DMF), γ-butyrolactone, 2-methoxyethanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP).
4. The coating agent for forming a large-area perovskite film according to claim 1, characterized in that: The crystallinity enhancer may be present in an amount of 15 to 40 mol % and the Lewis salt may be present in an amount of 40 to 100 mol % relative to 100 mol % of the perovskite precursor.
5. The coating agent for forming a large-area perovskite film according to claim 3, characterized in that: The solvent and the Lewis salt are included in a volume ratio of 1:0.06 to 0.
25.
6. A method for forming a large-area perovskite film, wherein the formation area is 200cm 2 The above method for large-area perovskite thin film is characterized in that A process comprising the following steps is carried out: Step 1, preparing the coating agent according to any one of claims 1 to 5; Step 2, forming a wet film of mesophase-crystallized perovskite by coating the coating agent on the upper portion of the substrate and drying the coating agent; and Step 3, performing an annealing process on the wet film to form a large-area perovskite film containing a perovskite compound represented by the following chemical formula 1: [Chemical formula 1] A m A’ 1-m B(X n X’ 1-n )3 In Chemical Formula 1, A is formamidine, ethylamine, guanidine or ethylenediamine, and A' is Cs + 、Na + , K + NH4 + or Rb + , B is Pb 2+ Sn 2+ , Pd 2 + , Cu 2+ ,Ge 2+ , Sr 2+ 、Cd 2+ , Ca 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ Sn 2+ , Yb 2+ or Eu 2+ , X and X' are each independently Cl - Br - or I - , m and n are rational numbers satisfying 0.7≤m≤0.9 and 0.1≤n≤0.
3.
7. The method for forming a large-area perovskite film according to claim 6, characterized in that: The upper part of the substrate coated with the coating agent is a Si thin film layer, a hole transport layer, an electron transport layer or a passivation layer.
8. The method for forming a large-area perovskite film according to claim 6, characterized in that: The above coating process is performed by knife coating, slot die coating, rod coating, inkjet coating or spray coating.
9. The method for forming a large-area perovskite film according to claim 6, characterized in that: The above drying is performed together with the coating process or after the coating process is completed.
10. The method for forming a large-area perovskite thin film according to claim 9, characterized in that: The drying is performed by an air knife blowing process to evaporate the solvent.
11. The method for forming a large-area perovskite thin film according to claim 6, characterized in that: The above annealing is performed by heat treatment at 120° C. to 180° C. for 5 minutes to 20 minutes.
Citation Information
Patent Citations
ACI type two-dimensional perovskite solar cell and preparation method thereof
CN110518128A
Perovskite ink formulations
CN114127978A
